Characterization of melanin from Exophiala mesophila with the prospect of potential biotechnological applications - Medina-Armijo, Cristy; Yousef, Ibraheem; Berná, Antonio; Puerta, Anna; Esteve-Núñez, Abraham; Viñas, Marc; Prenafeta-Boldú, Francesc X. (Frontiers in Fungal Biology, 2024)
Fungal melanin is an underexplored natural biomaterial of great biotechnological interest in different areas. This study investigated the physical, chemical, electrochemical, and metal-binding properties of melanin extracted from the metallotolerant black fungus Exophiala mesophila IRTA-M2-F10. Specific inhibitory studies with the tricyclazole and biochemical profiling of whole cells by synchrotron radiation-based Fourier-transform infrared spectral microscopy (SR-FTIRM) have indicated that 1,8-dihydroxynaphthalene might be the main precursor molecule of fungal melanin (DHN-melanin). An optimized extraction protocol was also implemented, and fungal melanin was characterized using an array of spectrophotometric techniques (UV-Vis, FTIR, and EPR) and by cyclic voltammetry (CV) experiments. The obtained results were benchmarked against those from two melanins comprising the precursor molecule L-3,4-dihydroxiphenylalanine (DOPA-melanin): extracts from the ink of the cephalopod Sepia officinalis and DOPA-melanin synthesized in the laboratory. The CV results of melanin extracts incubated with and without cell suspensions of the electroconductive bacterium Geobacter sulfurreducens are indicative of novel semiquinone/hydroquinone redox transformations specific for each melanin type. These interactions may play an important role in cation exchange for the adsorption of metals and in microbial interspecies electron transfer processes. The obtained results provide further evidence for the DHN-nature of E. mesophila melanin. The FTIR profiling of melanin extracts exposed to Cr(VI) as a model heavy metal, compared to unexposed melanin, resulted in useful information on the distinct surface-binding properties of fungal melanin. The Langmuir and Freundlicht adsorption isotherms of Cr(VI) onto fungal melanin were also determined and compared to bibliographic data. Altogether, the inherent properties of fungal melanin suggest its promising potential as a biomaterial for environmental applications.